The role of credibility and fundamentals in a funded pension system: a Markov switching analysis for Australia and Iceland - Mariangela Bonasia; Oreste Napolitano (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Since the turn of the millennium the problem of credibility of the social security system has spread to the private pension funds sector. This is evident for those countries, like Australia and Iceland, that have very large funded pensions assets as a result of strong pension reforms. The problem of trust could prevent pension fund investment from continuing to grow, weakening the privatization of the social security system. The objective of this study is to obtain new insights into the determinants of pension funds. We focus our analysis on the Australian and Icelandic experiences to study the credibility of pension fund performance and, as a consequence, of pension reform. Our credibility indicator is derived from a CAPM time-varying model. It can be used to investigate, using a Markov switching model, the linkages between economic fundamentals and the credibility of pension fund investment and the asymmetric effects of the fundamentals in the two regimes of low and hight credibillity. Our findings make a contribution to modelling policy credibility as a non-linear process with two distinct regimes. We also found large differences in the value of the coefficients for all macroeconomic variables between the low and high credibility regimes. This evidence strongly supports the hypothesis that the effects of macroeconomic fundamental variables on the level of credibility are asymmetric in all countries.
Keywords: E21; G23; H55; 330; Credibility; pension funds; Kalman filter; Markov switching model; Alterssicherung; Pensionsfonds; Rentenreform; Glaubwürdigkeit; Makroökonomischer Einfluss; Australien; Island